Stress in University Athletes: Review of the EEAD in Mexican Youth - Vanegas Farfano, Minerva; Ródenas Cuenca, Luis; Contreras Puente, María Elizabeth; Medina-Villanueva, Samantha (Psicumex, 2023)
Sports stress can be detrimental to an athletes’ performance. However, previous research has not always incorporated instruments designed for use in interventions. This study validates the sports stress rating scale in Mexican athletes and presents data on its convergent validity with the perceived stress scale. A cross-sectional study was carried out with 180 athletes (62.2% men and 37.8% women) from a northeastern university, who compete at different levels, with a mean age of 20.32 years (SD = 2.56), selected through convenience sampling. Furthermore, comparisons with Spanish samples indicated the same trend of unidimensionality and significantly higher scores in women than in men. The confirmatory factor analysis showed good fit indices; in addition to adequate reliability (EEAD, α = .80; PSS, α = .78) and a positive and significant correlation between them (r = .574, p <.001). The data confirms that the Mexican version of the EEAD is a valid, reliable instrument with a similar unidimensionality to similar Spanish speaking populations. Our findings suggest the scale is well suited for implementation of intervention studies of sports stress in Mexican university students.